2014
DOI: 10.1097/brs.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Countermeasures for Venous Thromboembolic Diseases Associated With Spinal Surgery

Abstract: DVT assessment using ultrasonography is important for proper management of VTE during the perioperative period of spinal surgery, especially for high-risk patients, such as those with advanced age or neurological deficit. The institutional protocol for VTE using pneumatic sequential compression device and compression stockings is effective, although the administration of chemoprophylaxis should be considered for high-risk patients, such as those with spinal tumors and spinal trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 32 publications
4
37
0
Order By: Relevance
“…After acute traumatic spinal cord injury, severe paralysis can be accompanied by reduced venous return, leading to the development of DVT. Furthermore, because a possible loss of the circulatory variation in hemostatic and fibrinolytic function has also been suggested in patients with spinal cord injury due to trauma, DVT is quite likely to develop in the [6,8,16,17]. The present study showed that female gender, advanced age, rapidly progressive myelopathy, low JOA score, and inability to walk were statistically significant risk factors for perioperative DVT development associated with degenerative cervical spine disease.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…After acute traumatic spinal cord injury, severe paralysis can be accompanied by reduced venous return, leading to the development of DVT. Furthermore, because a possible loss of the circulatory variation in hemostatic and fibrinolytic function has also been suggested in patients with spinal cord injury due to trauma, DVT is quite likely to develop in the [6,8,16,17]. The present study showed that female gender, advanced age, rapidly progressive myelopathy, low JOA score, and inability to walk were statistically significant risk factors for perioperative DVT development associated with degenerative cervical spine disease.…”
Section: Discussionsupporting
confidence: 51%
“…According to various reports, the incidence of DVT in patients who undergo spinal surgery ranges from 0.3 to 31% [4][5][6][7]. The incidence of DVT has been reported to vary depending on the type of disease, spinal level, method of surveillance, DVT prophylaxis, and surveillance period [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies were performed as prospective VTE management trials (2)(3)(4)(5). Therefore, we have performed perioperative DUS screening from 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas an impressive number of studies address the optimal dosage and timing of postoperative anticoagulants [4,26], we did not find any published material on the effectivity of the prescription process for anticoagulants in postoperative patients. Akeda et al [27] found, however, that the optimization of the perioperative management of anticoagulants and physical measures helped to reduce the rate of thromboembolic events in spinal surgery patients. When comparing our 2011 and 2013 data, we likewise observed a significant improvement which even affected the economic side of the issue.…”
Section: Discussionmentioning
confidence: 99%